Antitumor efficacy of arsenic/interferon in preclinical models of chronic myeloid leukemia resistant to tyrosine kinase inhibitors. Issue 16 (29th April 2019) - El Eit, Rabab; Itani, Abdul Rahman; Nassar, Farah; Rasbieh, Nagham; Jabbour, Mark; Santina, Ahmad; Zaatari, Ghazi; Mahon, François‐Xavier; Bazarbachi, Ali; Nasr, Rihab
Abstract : Background: Tyrosine kinase inhibitors (TKIs) are the standard treatment for chronic myeloid leukemia (CML). Despite their clinical success, TKIs are faced with challenges such as treatment resistance, which may be driven by kinase domain mutations, and frequent disease relapse upon the cessation of treatment. The combination of arsenic trioxide (ATO) and interferon‐α (IFN) was previously demonstrated to inhibit proliferation and induce apoptosis in CML cell lines, prolong the survival of primary wild‐type CML mice, and dramatically decrease the activity of leukemia‐initiating cells (LICs). Methods: The ATO/IFN combination was tested in vitro on imatinib (IMN)‐resistant K562‐R and Ar230‐R cells. 3‐(4, 5‐Dimethylthiazol‐2‐yl)‐2, 5‐diphenyl tetrazolium bromide and terminal deoxynucleotidyl transferase–mediated deoxyuridine triphosphate nick‐end labeling assays were used to evaluate proliferation and apoptosis, respectively. The acridine orange assay was used to assess autophagy, and quantitative reverse transcription–polymerase chain reaction was used to assess the involvement of the hedgehog (Hh) pathway. In vivo, a retroviral transduction/transplantation T315I BCR‐ABL CML mouse model was used to assay the effect of the treatment on survival, tumor burden (histopathology and blood counts), and LIC activity (secondary transplantation). Results: In vitro, ATO/IFN synergized to inhibit proliferation and induce apoptosis of IMN‐resistant cells with variant modes of resistance. Furthermore, the preclinical effects of ATO/IFN were associated with induction of autophagy along with inhibition of the Hh pathway. Most remarkably, ATO/IFN significantly prolonged the survival of primary T315I‐CML mice and displayed a dramatic impairment of disease engraftment in secondary mice, which reflected decreased LIC activity. Conclusions: Collectively, the ATO/IFN strategy has been demonstrated to have the potential to lead to durable remissions in TKI‐resistant CML preclinical models and to overcome various TKI‐specific mechanisms of resistance. Abstract : The combination of arsenic and interferon‐α overcomes 2 major challenges of chronic myeloid leukemia management with tyrosine kinase inhibitors: treatment resistance and persistence of leukemia‐initiating cells. This report shows that the combination is extremely successful in prolonging the survival of leukemic mice harboring the T315I mutation and in exhausting chronic myeloid leukemia–initiating cells.